Effectiveness of post-fire soil erosion mitigation treatments: A systematic review and meta-analysis - Girona-García, Antonio; Vieira, Diana C.S.; Silva, Joana; Fernández, Cristina; Robichaud, Peter R.; Keizer, J. Jacob (Earth-science reviews, 2021)
Wildfires are known to be one of the main causes of soil erosion and land degradation, and their impacts on ecosystems and society are expected to increase in the future due to changes in climate and land use. It is therefore vital to mitigate the increased hydrological and erosive response after wildfires to maintain the sustainability of ecosystems and protect the values at risk downstream from the fire-affected areas. Soil erosion mitigation treatments have been widely applied after wildfires but assessment of their effectiveness has been limited to local and regional-scale studies, whose conclusions may depend heavily on site-specific conditions. To overcome this limitation, a meta-analysis approach was applied to investigations of post-wildfire soil erosion mitigation treatments published in peer-reviewed journals. A meta-analysis database was compiled that consisted of 53 and 222 pairs of treated/untreated observations on post-fire runoff and erosion, respectively, extracted from 34 publications indexed in Scopus. The overall effectiveness of mitigation treatments, expressed as the quantitative metric ‘effect size’, was determined for both the runoff and erosion observations, and further analyzed for four different types of treatments (cover-based, barriers, seeding, and chemical treatments). The erosion observations involving cover-based treatments were analyzed for differences in effectiveness between 3 different types of mulch materials (straw, wood-based, and hydromulch) as well as between different application rates of straw and wood materials. Finally, the erosion observations were also analyzed for the overall effectiveness of post-fire year, burn severity, rainfall amount and erosivity, and ground cover. The meta-analysis results show that all four types of treatments significantly reduced post-fire soil erosion, but that only the cover and barrier treatments significantly reduced post-fire runoff. From the three different cover treatments, straw and wood mulches were significantly more effective in mitigating erosion than hydromulch. In addition, the effectiveness of both straw and wood mulches depended on their application rates. Straw mulching was less effective at rates below than above 200 g m−2, while mulching with wood materials at high rates (1300 to 1750 g m−2) produced more variable outcomes than lower rates. Results also suggest that the overall effectiveness of the treatments was greatest shortly after fire, in severely burned sites, providing or promoting the development of ground cover over 70%, and that it increased with increasing rainfall erosivity. It can be concluded that, in overall terms, the application of the studied post-fire erosion mitigation treatments represented a better choice than doing nothing, especially in sites where erosion is high. However, the meta-analysis highlights under-representation of studies on this topic outside of the USA, Spain and Portugal. It was also observed that most of the studies were conducted at hillslope scale and tested mulching (namely straw, wood and hydromulch) and/or barriers, while larger scales and other treatments were scarcely addressed. Further efforts need to be made in testing, from field and modeling studies, combinations of existing and/or emerging erosion mitigation treatments to ensure that the most adequate measures are applied after fires.